The Americanization of Emily [videorecording (DVD)] - Chayefsky, Paddy, 1923-1981; Garner, James, 1928-2014; Andrews, Julie; Douglas, Melvyn; Coburn, James; Grenfell, Joyce, 1910-1979; Windom, William, 1923-2012; Wynn, Keenan, 1916-1986; Huie, William Bradford, 1910-1986 (Archive collection., 2014)
"U.S. Navy honchos in World War II London have a humdinger of a war on their hands. Now they need a hero to go with it. They want the first American fatality of D-Day to be a sailor to glorify the Navy's effort." -- container.